Dielectric Relaxation and Collective Vibrational Modes of Double‐Perovskites A2SmTaO6 (A = Ba, Sr and Ca). Issue 8 (3rd June 2014) - Ghosh, Binita; Halder, Saswata; Sinha, Tripurari Prasad; Brennecka, G. L.
<x xml:space="preserve">Abstract</x> The crystal structures of the double‐perovskite oxide A2SmTaO6 series (AST, A = Ba, Sr, Ca) synthesized by solid‐state reaction technique are determined from X‐ray powder diffraction data. Rietveld refinements of the X‐ray diffraction data of the samples show that Ba2SmTaO6 (BST) crystallizes in cubic phase and Sr2SmTaO6 (SST) and Ca2SmTaO6 (CST) crystallize in monoclinic phase. Fourier transform infrared spectra show two primary modes of the samples at around 370 and 600 cm−1. The vibrational properties of the samples are studied by Raman spectroscopy taken at 488‐nm wavelength. Group‐theoretical study is performed to assign the different vibrational modes of the samples in accordance with structural symmetry. The observed shifts of some vibrations in the SST and CST w.r.t. BST upon changing the A cation are tentatively explained. Dielectric spectroscopy is applied to investigate the ac electrical conductivity of AST in different temperatures between 303 and 673 K and in a frequency range of 42 Hz–1 MHz. The complex impedance plane plots show that the relaxation (conduction) mechanism in these materials is purely a bulk effect arising from the semiconductive grains. The relaxation mechanism of the samples is modeled by Cole–Cole equation. The frequency‐dependent conductivity spectra are found to follow the power law.